Direct Synthesis of Amides from Carboxylic Acids and Amines by Using Heterogeneous Catalysts: Evidence of Surface Carboxylates as Activated Electrophilic Species. Issue 10 (1st July 2013) - Deiana, Chiara; Sakhno, Yuriy; Fabbiani, Marco; Pazzi, Marco; Vincenti, Marco; Martra, Gianmario
<x xml:space="preserve">Abstract</x> Amide synthesis: In situ IR spectroscopy and HRMS provided evidence of the activation of surface carboxylates at mild temperatures (about 323 K) for the direct synthesis of amides from carboxylic acids and amines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>